2011
DOI: 10.1074/jbc.m110.193854
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulation of Ras-GTP Is Linked to Signal Transduction through RAF Kinase

Abstract: Ras is a key signal transduction protein in the cell. Mutants of Gly 12 and Gln 61 impair GTPase activity and are found prominently in cancers. In wild type Ras-GTP, an allosteric switch promotes disorder to order transition in switch II, placing Gln 61 in the active site. We show that the "on" and "off" conformations of the allosteric switch can also be attained in RasG12V and RasQ61L. Although both mutants have similarly impaired active sites in the on state, RasQ61L stabilizes an anti-catalytic conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(123 citation statements)
references
References 40 publications
5
117
1
Order By: Relevance
“…The G12D and Q61 mutants directly impair the chemistry of GTP hydrolysis by either placing a negative charge right over the nucleotide or removing an important catalytic residue. Furthermore, Q61L is also unique in that it has a strong tendency to stabilize the T state in the anticatalytic conformation when bound to RAF, abolishing even the slow hydrolysis rate observed in the uncomplexed protein (14,15,73). In the absence of binding partners, both switch I and switch II are disordered in solution (11,61), and they become stabilized by interactions with other proteins (15,30,76,77).…”
Section: Effects Of Oncogenic Mutations On Intramolecular Communicatimentioning
confidence: 99%
See 4 more Smart Citations
“…The G12D and Q61 mutants directly impair the chemistry of GTP hydrolysis by either placing a negative charge right over the nucleotide or removing an important catalytic residue. Furthermore, Q61L is also unique in that it has a strong tendency to stabilize the T state in the anticatalytic conformation when bound to RAF, abolishing even the slow hydrolysis rate observed in the uncomplexed protein (14,15,73). In the absence of binding partners, both switch I and switch II are disordered in solution (11,61), and they become stabilized by interactions with other proteins (15,30,76,77).…”
Section: Effects Of Oncogenic Mutations On Intramolecular Communicatimentioning
confidence: 99%
“…5A). It has been shown that both G12V and Q61L can attain the R and T states of the allosteric switch under circumstances where switch I is in state 2 (14), as it is when bound to RAF, and it is likely that other oncogenic mutants can as well.…”
Section: Effects Of Oncogenic Mutations On Intramolecular Communicatimentioning
confidence: 99%
See 3 more Smart Citations